KOMUNITAS MAKROZOOBENTHOS PADA LOKASI BUDIDAYA IKAN DALAM KERAMBA DI SUNGAI KOMERING - Hoyauna, Hoyauna; Hilda, Hilda; Husnah, Husnah (Jurnal Ilmu-Ilmu Perikanan dan Budidaya Perairan, 2003)
Study on macrozoobenthos community lived under fish cage culture had been carried out at Komering river in October 2001 and January 2002. The objective of this study was to know macrozoobenthos community lived under fish cage culture area and compared it with non fish cage culture area. Two sampling point in each station. The result of this study revealed that macrozoobenthos found in station I and II was 18 and 21 species, respectively. The abundance of macrozoobenthos in October 2001 in station I was 3064 ind/m2 and in station II was 200 ind/m2, while the abundance on both stations in January 2002 was relatively similar which was 1370 ind/m2 in station I and 1415 ind/m2 in station II. Diversity index was lower in station I (1,61-1,73) than that in station II (1,80-1,96). Similarity index in both stations were lower in October 2001 (13,55%) than January 2002 (44,95%). The organic matter content of sediment in station I (C=0,39%, N=10,86%, P2O5 = 159,50 mg P2O5/100 g soil) was higher than in station II which relate to the presence of species of Tubificidae (Brancura sp, Nais sp, and Tubifex sp), Diptera (Subfamili Chironominae and Chironomus sp) and Mesogastropoda (Melanoides tuberculata). The study indicated that the presence of cage culture affected macrozoobenthos composition, abundance, diversity and homegenity indexes.Keywords : macrozoobenthos, community, fish cage, Komering river.